Contemporary Greek male homosexualities : Greek gay men's experiences of the family, the military and the LGBT movement - Dendrinos, Panayis (2008)
This thesis provides an ethnographic analysis of how Greek gay men experience the ways in which their sexuality is subject to ‘negotiation’ in the family and the military, how these ‘negotiations’ influence and sometimes even inhibit the creation of an LGBT movement. The experiences of my ethnographic informants produced little material for generalisations but the diversity of their voices suggests that they are constantly fighting between the desire to belong and the wish to remain different. I argue that the theoretical framework of timi and dropi (honour and shame) can still be a valuable explanatory tool for an understanding of Modern Greek homosexualities. Yet, this thesis offers a critique of this paradigm for its neglect to account for the possible ways in which the sexual contact of the men in a family may occasionally be seen as a threat to the family’s honour. As a result, silence becomes a defence mechanism that many of my gay interlocutors and their families employ to deal with homosexuality. This varied silence often inhibits the sense of pride in the man’s homosexuality and in turn prevents him from joining the movement that would require him to be vocal about his sexual self. The military experiences of my interlocutors, on the other hand, challenge the assumption that the military is a strictly heterosexual space. What they often describe as the ‘homo-social’ environment of the military acted as a catalyst for several of them to come to terms with their homosexuality. The thesis also explores the history of Greek LGBT activism from its inception in 1976 to today and examines the reasons behind its limited success in capturing the hearts and minds of my interlocutors